INORGANIC PHOTOCATALYSTS FOR SOLAR ENERGY CONVERSION - Nagaveni V B (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This study explores the Inorganic Photocatalysts for Solar Energy Conversion. Inorganic photocatalysts have emerged as a promising solution for solar energy conversion, playing a crucial role in addressing global energy demands and environmental challenges. These materials facilitate the conversion of solar energy into chemical energy through processes such as water splitting for hydrogen production, carbon dioxide reduction, and organic synthesis. The mechanism of photocatalysis involves the absorption of light, which generates electron-hole pairs within the photocatalyst. These excited electrons can engage in reduction reactions, while the resulting holes can drive oxidation processes, enabling various chemical transformations. Among the most extensively studied inorganic photocatalysts are metal oxides such as titanium dioxide (TiO₂), zinc oxide (ZnO), and iron oxide (Fe₂O₃), alongside metal sulfides, perovskites, and nitrides. Each of these materials exhibits unique properties, such as varying band gaps and surface areas, which influence their photocatalytic efficiency. Recent advancements in material science have led to the development of novel photocatalysts with enhanced performance, including composite structures and doped materials that improve light absorption and charge carrier dynamics. Despite the significant progress, challenges remain in terms of stability, scalability, and a comprehensive understanding of reaction mechanisms. Improving the durability of photocatalysts under operational conditions is essential for practical applications, while scalable production methods are necessary for commercial viability. Future research directions focus on integrating photocatalysts with solar cells to create tandem systems, as well as exploring new materials and strategies for enhancing photocatalytic activity. Overall, inorganic photocatalysts represent a vital component of the transition toward sustainable energy systems, offering pathways for clean hydrogen production and effective carbon dioxide utilization. Continued exploration and innovation in this field hold great promise for mitigating climate change and promoting a more sustainable energy landscape.